A Narrative Review of Internet Use, Interpersonal Connectedness, and Sexual Behaviour Among Gay, Bisexual and Other Men Who Have Sex With Men. Issue 2 (28th January 2020) - Card, Kiffer G.; Lachowsky, Nathan J.; Gislason, Maya G.; Hogg, Robert S.; Roth, Eric A.
ABSTRACT: Researchers have often considered the impact that online dating has had on gay communities; with some arguing that changes in social behavior may impact the spread of HIV. However, these conclusions are based on the premise that the Internet has fundamentally changed the way gay and bisexual men connect with their communities. Addressing this issue, we searched the PubMed and Web of Science databases for studies examining Internet use and interpersonal connectedness among gay and bisexual men to determine whether those who used the Internet to find sexual partners exhibited different patterns of community connectedness. Though sporadic, findings suggest that Internet use may be associated with lower gay identity, community attachment, and social embeddedness. However, recent reports have suggested that online sex seeking might be associated with greater, not less, interpersonal connectedness. We conclude that additional longitudinal analyses and consistent measurement of gay men's social behavior are needed to draw more definite conclusions.